2019
DOI: 10.15847/obsobs13120191278
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlocal Journalism and PR: Diversity in Roles and Interactions

Abstract: Hyperlocal media has repeatedly been framed as a potential saviour of local journalism, but the democratic and civic role that often is ascribed to hyperlocals is not obvious or uncomplicated. The hyperlocals' vulnerable economic situation makes them dependent on free content, for example material produced by local councils or organizations. This paper investigates the role of hyperlocal media entrepreneurs and their interaction with local councils and other stakeholders. We examine how the hyperlocal media en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The selection of the three countries studied was motivated mainly by the authors' access to the empirical data in these countries. At the same time, the authors' previous research (Dovbysh & Mukhametov, 2020;Jangdal et al, 2019) demonstrates that the local media in these three countries have both differences and similarities which justify a comparative analysis.…”
Section: The Study In Contextmentioning
confidence: 94%
“…The selection of the three countries studied was motivated mainly by the authors' access to the empirical data in these countries. At the same time, the authors' previous research (Dovbysh & Mukhametov, 2020;Jangdal et al, 2019) demonstrates that the local media in these three countries have both differences and similarities which justify a comparative analysis.…”
Section: The Study In Contextmentioning
confidence: 94%
“…With this in mind, Stúr, Jangdal, and Nilsson (2018) discuss the relationship between hyperlocal media and city councils through the vision of their entrepreneurs. It is shown that the watchdog function that hyperlocal media can perform depends on the relationship they maintain with the local government.…”
Section: Community Oriented Journalism and Informational Gapmentioning
confidence: 99%
“…Most hyperlocal operations in Sweden are less than ten years old. The founders range from journalists to "non-professional amateurs and enthusiasts" (Leckner, Tenor, and Nygren 2017, 4) but have in common that they consider their role in society important (Jangdal, Cepaite Nilsson, and Stúr 2019). Some predict growth in this sector by anticipating that layoffs in legacy media could mean more journalists may venture into their own independent digital news start-ups (DeRienzo and Smith 2016).…”
Section: Hyperlocals In the New Media Landscapementioning
confidence: 99%